NPK fertilizer on peanut and maize cultivar under agroforestry system. (March 2019) - Purnomo, D; Budiatuti, Mth S; Sakya, AT
Abstract: According its characteristics, the sengon (Albizia chinensis) forests have potenty for crop cultivation as Agroforestry (AF) system. Sengon canopy at 3-4 years old has Fraction radiation transmission (FRT) about 80%, moreover soil fertility under tree has medium, especially, N (Nitrogen) and P (Phospor), and low K (Potassium) content. This study was performed to observe the effect of NPK fertilizer on maize and peanut, representing C4 and C3 crop type, which were cultivated between sengon stands. The study was conducted under 3, 4, and 5 years old of sengon stand. In each sengon stands age group, the experiment was designed as Randomize Complete Block Design (RCBD) consists of 7 factors treatment. The treatments were without fertilizer as control, P and K fertilizer (3 levels), N, P, and K fertilizer (3 levels), then data were analyzed using orthogonal contrast. The result showed that peanuts were cultivated successfully in all of sengon stand (3, 4, and 5 years old). Whereas maize only grow well under 3 years old of sengon stand. The application of P and K fertilizer were able to increase the growth and yield of both crops and will be improved if N was applied at the same time.